INVESTIGATIONS ON THIXOJOINING PROCESS OF STEEL COMPONENTS - M.N. Mohammed; M.Z. Omar; J. Syarif; Z. Sajuri; M.S. Salleh; K.S. Alhawari (Journal of Mechanical Engineering and Sciences, 2013)
This research is to develop a carbon composite prepared from carbon coir fibers that is reinforced with epoxy resin. Carbon coir fibers were taken from three types of coir fiber specifically designated as CKCF, CYCF and CRCF. The samples were prepared using epoxy resin reinforced with carbon at different weight percentages for three types of coir fiber starting with 0wt.%, 2wt.%, 4wt.%, 6wt.%, 8wt.% and 10wt.%. The mechanical properties such as tensile stress and impact strength were used to characterize all the samples. The morphological study of reinforced samples was also conducted in this research using a SEM machine. The characteristics of all the composite materials were also investigated and discussed. It was determined that the CKCF sample exhibited better mechanical properties than the other coir fiber composites, having a higher average tensile stress value at 11.80MPa and higher impact strength values ranging from 268J to 276J at different carbon content. CKCF with 10wt% AC content had a tremendous impact strength compared with CYCF and CRCF.